Ministry and Ministries in the Church - Vitali, Dario (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2022)
This article examines the long-standing issue of ministry and the ministries in the Church. The hermeneutical principle providing the foundation for this contribution is the correspondence between model of the Church and model of ministry. Where they do not correspond to oneanother, both suffer. The article takes an historical approach to demonstrate how ministry has undergone a process of clericalization by which the two models have been identified in the pyramidal/clerical structure of the Church. This process sheds light on the difficulty of shedding that model, as demonstrated by the story of the ministries instituted fifty years after the publication of Ministeria Quaedam. The proposed solution moves in the direction of recovering the relationship between common priesthood and ministerial priesthood (cf. LG 10): the baptismal ministries would be rooted in the common priesthoodas a particular form of participation in the priesthood of Christ.